Legal Protection For Children in The Womb Outside Of Legal Marriage - Botu, Susanti I (Damhil Law Journal, 2022)
This article explains the law on children out of wedlock or children out of wedlock that are legitimate. Initially, the laws and regulations in Indonesia only regulated the status of legitimate children, because based on a legal marriage, all rights are attached to the rights of children. Meanwhile, children out of wedlock or children out of wedlock are only entitled to civil law protection from the mother's side or the mother's family.Â  The research method used is to use normative literature research methods by using various literature in the form of library materials which are library research or secondary data. The results of the research are as recognized by the Convention on the Rights of the Child which has been ratified by Indonesia through Presidential Decree No. 36 of 1990. The ambiguity of the existing law regarding extra-marital children requires the harmonization of legal norms to ensure justice, expediency, and legal certainty. Initially, Indonesian law only protected the legal status of legitimate children born in marriage, so that illegitimate children only received civil protection from their mother or their mother's family. However, Constitutional Court Decision No. 46/PUU-VIII/2010 has equalized the legal status of legitimate and illegitimate children, ensuring they receive the same legal protection. This decision immediately overturned previous provisions that limited civil rights to the mother's side, granting equal legal standing to illegitimate children.